ALMOST THE SAME BUT NOT WHITE: MITO GREGO E DRAMATURGIA DE AUTORIA NEGRA EM OBRAS PÓS-COLONIAIS EM LÍNGUA INGLESA NO CARIBE E NA ÁFRICA - CARVALHO, CAROLINA FILIPAKI DE (2024)
In this research, anglophone plays which aim to dialogue with canonical texts written by black authors in the post-colonial context are analyzed, namely: Women of Owu (2016), by Femi Osofisan, from Nigeria, and The Odyssey: A stage version (1993), by Derek Walcott, from Saint Lucia, which are, respectively, rewritings of the Greek works The Trojan Women, by Euripides dating from 416 B.C. and The Odyssey, by Homer, from the 8th century BC. Adopting the post-colonial perspective to analyze the works, the aim was to analyze how the subversive use of the English language operates in the demarcation of post-colonial characteristics, to impose the marks of négritude in these works, according to the concept of négritude by Aimé Cesaire (1978). The theoretical foundation stem from The Empire writes back, by Ashcroft, Griffiths and Tiffin (2004), given its importance for the discussion of post-colonial literary works in the English language. Theoretical support is also found in scholars of post-colonialism from different areas, including Frantz Fanon (2020, 2021, 2022), Homi Bhabha (1984, 1991, 1998), Edward Said (1995), Édouard Glissant (2005), Ngugi wa Thiong'o (1986), Gayatri Spivak (2010), bell hooks (2017, 2019, 2020), Grada Kilomba (2019), Leda Maria Martins (1995, 1997, 2021), Décio Torres Cruz (2016), McLeod (2010), and Thomas Bonnici (2005, 2009, 2012), among others. The analysis demonstrated that the intertextual dialogue with classic texts proposed by the authors aims to create a unique aesthetic and to conquer the power of speech by the colonized black subject. The authors use appropriation and abrogation as resources to make subversive use of the English language and literature as a tool of imperialist culture. It was also observed that the metonymic gap, the appropriation of space and religious discourse are fundamental for the construction of the plays and for exploring the potential for discursive resistance of these literary pieces. The analysis of the treatment given to female characters from postcolonial feminist criticism perspective demonstrated that the authors were successful in constructing texts with a decolonial outilne; however, female characters exemplify the double colonization of women, who succumb to colonial and patriarchal power. From the perspective of Walter Benjamin (1987) and Terry Eagleton (1993), it is considered that the linguistic and literary resources used by the authors contribute to the rewriting of History, offering voice to the defeated and visibility to perspectives silenced in official History. Based on the concept of sly civility, by Homi Bhabha (1998), it was found that the authors also promote resistance based on the native refusal to satisfy the colonizer's demand in the use of their cultural artifacts.